The Relationship Between Price Discounts and Impulsive Purchase: The Mediating Role of Positive Emotions - Aliwinoto, Christine; Hadianto, Bram; Tjiptodjojo, Kartika Imasari (Journal of Business and Economics Research (JBE), 2024)
This study aims to test and analyze the effect of price discounts on impulse buying and positive emotions (PE), as well as the influence of PE on impulse buying. Besides, examining and analyzing the PE to mediate the relationship between price discounts and impulse buying becomes another intention. The population comes from Generation Z, born between 1995 and 2009, who purchased goods in the Yogya Department Store in Bandung City. Moreover, a purposive sampling method is utilized to sample them. Fortunately, this study can collect 207 people based on the survey. Therefore, this study uses a covariance-based structural equation model and Sobel test. After statistical testing is complete, this study demonstrates (1) no effect of price discounts on impulsive buying, (2) a positive influence of price discounts on PE, (3) a positive relationship between PE and impulsive purchase, and (4) the mediating effect of PE on the association between price discounts and impulse buying. Additionally, the R-square in the positive emotion and impulsive models is 0.801 and 0.148, respectively. As an implication, this study suggests that department stores apply price discounts on goods to elevate positive feelings with the help of salespersons providing excellent services, creating impulsive purchases after employees receive salaries.